2022
DOI: 10.3389/fimmu.2022.898561
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of KRAS Mutational Regression in Oligometastatic Patients

Abstract: BackgroundWe previously reported rare regressive genetic trajectories of KRAS pathogenic mutations as a specific hallmark of the genuine oligometastatic status in colorectal cancer (CRC).MethodsSurvival and prognostic impact of disease extent in 140 metastatic CRC patients were evaluated through the Kaplan–Meyer curves and the Log-Rank test. KRAS mutations were assessed through the Illumina NovaSeq 6000 platform and TruSight™ Oncology 500 kit. HLA typing was carried out by PCR with sequence-specific oligonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Finally, we previously observed a higher prevalence of the HLA-C7 allele in OMD from CRC patients. This data could support the enhanced presentation of specific tumor antigens and align with specific immunological phenomena underlying the oligo-metastatic status [60].…”
Section: Genetics Of Oligo-metastatic Diseasesupporting
confidence: 66%
“…Finally, we previously observed a higher prevalence of the HLA-C7 allele in OMD from CRC patients. This data could support the enhanced presentation of specific tumor antigens and align with specific immunological phenomena underlying the oligo-metastatic status [60].…”
Section: Genetics Of Oligo-metastatic Diseasesupporting
confidence: 66%
“…Furthermore, as already reported in other settings, in contrast with the common knowledge suggesting that gene mutations constantly prompt cell transformation and metastases, some driver gene mutations ( PBRM1 and SETD2 ) were associated with attenuated progression and OMD. More studies have been reported in colorectal cancer (CRC) where molecular subtyping (“canonical” and “immune” subtypes) [ 90 ], regression of key-driver gene mutations ( KRAS , PIK3CA ) [ 91 ], high level of T-cell infiltration into metastases [ 92 ], high level of peripheral cytotoxic T-cells [ 93 ], specific gene mutations ( ERBB2 ) [ 92 ] correlates with the OMD phenotype. In particular, in our previous reports [ 91 , 92 ], we provided an evolutionary and dynamic analytic perspective, highlighting that comparing primary and metastatic lesions could assist in identifying the true de novo oligo-metastatic behavior.…”
Section: Biomarkers Of Omdmentioning
confidence: 99%
“… The patients with these characteristics develop poly-metastatic widely diffusive disease. Ottaiano, 2022 [ 93 ] Colorectal cancer. KRAS regression from primary to metastatic lesions.…”
Section: Biomarkers Of Omdmentioning
confidence: 99%
“…The extended studies regarding distinctive molecular profile of oligometastatic CRC have demonstrated that oligometastatic CRC is a specific disease having a potential of cure and not simply an evolutionary step towards polymetastatic disease, which has more aggressive biological behavior [ 207 , 208 , 209 , 210 , 211 , 212 ]. Loss of KRAS and SMAD4 mutations characterizes the oligometastatic disease while a progressive mutational evolution (gain in KRAS, PI3KCA, BRAF, and SMAD4) is observed in polymetastatic evolving disease.…”
Section: Future Directionsmentioning
confidence: 99%